Safety and Efficacy of Drug Holidays for Women with Sexual Dysfunction Induced by Selective Serotonin Reuptake Inhibitors (SSRIs) Other than Fluoxetine: An Open-Label Randomized Clinical Trial - Elham Lalegani; Negin Eissazade; Mohammadreza Shalbafan; Razieh Salehian; Seyed Vahid Shariat; Sanaz Askari; Laura Orsolini; Shiva Soraya (Brain Sciences, 2023)
Selective serotonin reuptake inhibitors (SSRIs) are the cornerstone of psychopharmacology. However, they cause side effects such as sexual dysfunction, leading to the discontinuation of treatment. We aimed to investigate the efficacy and safety of drug holidays for women experiencing sexual dysfunction Induced by SSRIs other than fluoxetine. This study was an 8-week randomized, open-label, controlled trial including married women aged between 18 and 50 years who had experienced sexual dysfunction while undergoing treatment with SSRIs. The intervention group implemented drug holidays by not taking medications on Thursdays and Fridays, while the control group continued regular medication use. The female sexual function index (FSFI) and the 28-question general health questionnaire (GHQ-28) were administered to assess sexual function and mental health, respectively. A total of 50 participants completed the trial. The drug holidays’ group showed significant improvements in arousal (p < 0.001), desire (p = 0.001), orgasm (p < 0.001), satisfaction (p < 0.001), lubrication (p = 0.021), and overall sexual health (p < 0.001). The between-group difference of pain was significant (p < 0.001), despite no significant within-group change. Mental health improved in both groups, despite no significant between-group difference. No major adverse effects were reported. Drug holidays did not introduce immediate safety concerns or significant adverse effects during the timeframe of eight weeks, suggesting that it may be a safe and effective strategy for managing SSRI-induced sexual dysfunction in women, alongside improving mental health. Further research is needed to reach a definitive conclusion.